2018
DOI: 10.18203/2319-2003.ijbcp20184328
|View full text |Cite
|
Sign up to set email alerts
|

Disposition kinetics, in vitro plasma protein binding and tissue residues of tilmicosin in healthy and experimentally (CRD) infected broiler chickens

Abstract: Background: Several studies assayed the pharmacokinetics of tilmicosin in broilers at a dosage of (25mg/kg.b.wt.). The aim of this study was to investigate the pharmacokinetics and tissue residues of tilmicosin following single and repeated oral administrations (25mg/kg.b.wt.) once daily for 5 consecutive days in healthy and experimentally Mycoplasma gallisepticum and E. coli infected broilers.Methods: After oral administrations of tilmicosin (25 mg/kg.b.wt.) one ml blood was collected from the right wing vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
6
1
1
Order By: Relevance
“…Regarding of tilmicosin pharmacokinetic after single intracrop administration, the drug was firstly detected at 0.25 h after administration, peaked at 2h post-administration, and decreased gradually till reaching the lowest drug concentration achieved at 24 hr post drug administration. The result of Cmax (1.49 µg/ml), reported in the present study was found to be closely connected to that testified by Attia et al(2018) for tilmicosin in broilers (1.06 µg/ml) and for tilmicosin in rabbits (1.31µg/ml) at 12.5 mg/kg but lower than that stated by Abu-Basha et al(2007) for tilmicosin (Pulmotil AC ® ) in broilers (2.12 μg/ml) at 30 mg/kg, and that reported by Gallina et al,(2010). This discrepancy could be attributed to dose, species differences, and/or the drug assaying process.In contrast, time to peak plasma level (tmax 3.01) was longer compared to that determined by McKay et al (1996) for tilmicosin in rabbits (2h), Abu-Basha et al (2007) for tylosin in chicken (2.36 h), Attia et al (2018) and Shaban et al (2019) for tilmicosin in broilers (2.56h and 2.1h, respectively) but lower than that estimated by Abu-Basha et al (2007) in broilers for tilmicosin (Pulmotil AC ® ) (5.82h) at 30 mg/kg.…”
Section: Pharmacokinetic Of Single Intracrop Tilmicosin Administration In Healthy and Nri Broilerssupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding of tilmicosin pharmacokinetic after single intracrop administration, the drug was firstly detected at 0.25 h after administration, peaked at 2h post-administration, and decreased gradually till reaching the lowest drug concentration achieved at 24 hr post drug administration. The result of Cmax (1.49 µg/ml), reported in the present study was found to be closely connected to that testified by Attia et al(2018) for tilmicosin in broilers (1.06 µg/ml) and for tilmicosin in rabbits (1.31µg/ml) at 12.5 mg/kg but lower than that stated by Abu-Basha et al(2007) for tilmicosin (Pulmotil AC ® ) in broilers (2.12 μg/ml) at 30 mg/kg, and that reported by Gallina et al,(2010). This discrepancy could be attributed to dose, species differences, and/or the drug assaying process.In contrast, time to peak plasma level (tmax 3.01) was longer compared to that determined by McKay et al (1996) for tilmicosin in rabbits (2h), Abu-Basha et al (2007) for tylosin in chicken (2.36 h), Attia et al (2018) and Shaban et al (2019) for tilmicosin in broilers (2.56h and 2.1h, respectively) but lower than that estimated by Abu-Basha et al (2007) in broilers for tilmicosin (Pulmotil AC ® ) (5.82h) at 30 mg/kg.…”
Section: Pharmacokinetic Of Single Intracrop Tilmicosin Administration In Healthy and Nri Broilerssupporting
confidence: 91%
“…The result of Cmax (1.49 µg/ml), reported in the present study was found to be closely connected to that testified by Attia et al(2018) for tilmicosin in broilers (1.06 µg/ml) and for tilmicosin in rabbits (1.31µg/ml) at 12.5 mg/kg but lower than that stated by Abu-Basha et al(2007) for tilmicosin (Pulmotil AC ® ) in broilers (2.12 μg/ml) at 30 mg/kg, and that reported by Gallina et al,(2010). This discrepancy could be attributed to dose, species differences, and/or the drug assaying process.In contrast, time to peak plasma level (tmax 3.01) was longer compared to that determined by McKay et al (1996) for tilmicosin in rabbits (2h), Abu-Basha et al (2007) for tylosin in chicken (2.36 h), Attia et al (2018) and Shaban et al (2019) for tilmicosin in broilers (2.56h and 2.1h, respectively) but lower than that estimated by Abu-Basha et al (2007) in broilers for tilmicosin (Pulmotil AC ® ) (5.82h) at 30 mg/kg. The cause of these differences could be attributed to species and dose variation, medication administration routes, and the presence of food in the chicken crop, which would alter crop motions, as well as the consistency of the feed, which could affect crop emptying.…”
Section: Pharmacokinetic Of Single Intracrop Tilmicosin Administration In Healthy and Nri Broilerssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings were in concordance with those of Salman et al (2016) who reported that the serum concentrations of tylvalosin was significantly lower in M. gallisepticum infected chickens compared to healthy ones. Similarly, Attia et al (2018) mentioned that the serum levels of tilmicosin were markedly higher in healthy chickens than in M. gallisepticum and Escherichia coli infected ones.…”
Section: Discussionmentioning
confidence: 97%